A new magnesium-containing aluminophosphate with a zeolite-like structure. Issue 2 (22nd December 2015) - Jiao, Xuejiao; Wang, Yanyan; Mu, Ying; Sun, Yanjun; Li, Jiyang
Abstract : A novel Mg-containing aluminophosphate JU96 is presented, which exhibits a new 4-connected zeolite-like topology with intersecting 8-ring channels. Abstract : A novel Mg-containing aluminophosphate |C4 H12 N2 |[Mg2 Al6 (PO4 )8 (H2 O)4 ] (JU96) has been hydrothermally synthesized using piperazine as a structure-directing agent. Its framework, constructed by the connection of AlO4 /MgO4 (H2 O)2 polyhedra and PO4 tetrahedra, exhibits a new 4-connected zeolite-like topology with intersecting 8-ring channels. Such a framework contains unique [4 4 ·6 6 ·8 6 ] cages that are occupied by diprotonated piperazine cations. Study shows that the presence of Mg atoms and the pH value of the reaction gel have a vital effect on the formation of JU96.